PENGEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI MEDIA GERABAH - Ulfa; Winarti (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The purpose of this study was to determine the creativity of children through pottery media. Researchers take action in an effort to improve children's creative abilities through the method of playing with natural materials of clay. Researchers took natural clay as a playing medium because clay is safe for children, easy to obtain, does not pollute the environment, and from this clay media can produce products such as pottery (various kinds of household utensils, piggy banks, flower pots), tiles and stones. brick. Meanwhile, the scope of this research is limited to the influence of pottery media on the creative development of children aged 5-6 years in Dharma Wanita Ngumpakdalem Kindergarten. The approach used in this study is a qualitative approach. Meanwhile, the type of research that will be used by researchers is descriptive research. The data collection technique used by researchers is to use observation, discussion and documentation. The results of the research on the creativity of children in class B of Dharma Wanita Numpakdalem Kindergarten showed good development, this was evident from the total number of students who were able to participate in these activities were 100% (15 children). Besides that, it can be seen from the enthusiasm, interest, and enthusiasm of students in playing clay activities to make pottery